(untitled) (Bangladesh Journal of Medical Science, 2012)
Urinary calculi are rarely seen in the urethra and are usually encountered in men with urethral stricture or diverticulum. The case of a 23-year-old woman presented with acute retention of urine associated with recurrent urinary tract infection. Cystoscopy was done and the stone was removed. The patient has been well, with no dysuria, and incontinence for 3-month follow-ups. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8724 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 137-138